1999
DOI: 10.1111/j.1471-0528.1999.tb08179.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial comparing transvaginal ultrasound, outpatient hysteroscopy and endometrial biopsy with inpatient hysteroscopy and curettage

Abstract: Objective To compare the use of outpatient and inpatient procedures in the investigation of abnormal Design A randomised controlled trial.Setting Two university teaching hospitals.Participants Four hundred women with abnormal uterine bleeding (postmenopausal bleeding, menorrhagia, intermenstrual bleeding, postcoital bleeding, or irregular periods) above the age of 35 years, between June 1993 and January 1995.1. Incidence of detection of abnormal pathology by vaginal ultrasound, outpatient hysteroscopy and endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
2
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(60 citation statements)
references
References 26 publications
1
52
2
4
Order By: Relevance
“…Shwarzler [2] studied a total of 104 patients with age varying from 26 to 79 years. Tahir [3] studied 400 women all above age of 35 years. Giannninoto [4] performed diagnostic hysteroscopy in 512 women with complaints of AUB, age ranging from 38 to 80 years and with mean age of 63 years.…”
Section: Discussionmentioning
confidence: 99%
“…Shwarzler [2] studied a total of 104 patients with age varying from 26 to 79 years. Tahir [3] studied 400 women all above age of 35 years. Giannninoto [4] performed diagnostic hysteroscopy in 512 women with complaints of AUB, age ranging from 38 to 80 years and with mean age of 63 years.…”
Section: Discussionmentioning
confidence: 99%
“…This increased risk is almost, if not totally, eliminated if appropriate cyclic or continuous progestins are added to the regimen 17 (Class 4), 23 (Class 1a), 24 (Class 1b). However, a number of features may affect these risks, including the dose of the estrogen, and the dose, route, and regimen used to administer the progestin.…”
Section: Hormone Replacement Therapymentioning
confidence: 99%
“…Office-based sampling is usually performed with disposable catheters that allow for the application of suction to obtain a specimen. Any method of sampling the endometrial cavity misses a proportion of endometrial cancers 24 (Class 1b), 47,48 (Class 3), 49 Collectively, these data would suggest that women with "nondiagnostic" endometrial biopsy specimens should have additional uterine evaluations with TVUS, contrast sonography, hysteroscopy, or a combination of any of these procedures.…”
Section: Histologic Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Office endometrial sampling with narrow disposable catheters has been generally demonstrated to be equivalent to the so-called "formal" dilation and curettage for diagnosing endometrial carcinoma. [38][39][40] …”
Section: Histologic Assessmentmentioning
confidence: 99%